Sexual dimorphism in stapes by discriminant functional analysis - Singh, Kamal; Rohilla, Aarti (International Journal of Research in Medical Sciences, 2017)
Background: Sexing of human skeleton is highly contested subject and is usually done by using morphological and metrical traits of big intact bones like skull, mandible, pelvis and long bones etc.1 The stapes remains well protected by being housed in the middle ear, even in the mutilated bodies. Methods: The morphometric study of the 120 human stapes bones from 60 unidentified cadavers was aimed to know the presence of sexual dimorphism. Results: The weight and measurements of footplate could be a good criterion for determining percentage accuracy as male and female respectively and could be used as a potential tool for determination of sex. Conclusions: The study of normal dimensions and indices of stapes will provide insight to the forensic experts for deciding the sex of an individual in the disputed cases. Our findings are the results for guidance and future manipulation in the forensic and legal medicine.